Early continuous blood purification affects TNF‐α, IL‐1β, and IL‐6 in patients with severe acute pancreatitis via inhibiting TLR4 signaling pathway - Zhi‐Peng Chen (Kaohsiung Journal of Medical Sciences, 2022)
Abstract To exploit whether early continuous blood purification (CBP) inhibits the Toll‐like receptors 4 (TLR4) signaling pathway in the peripheral blood of patients with severe acute pancreatitis (SAP) and whether it affects the abundance of inflammatory factors; 130 SAP patients were randomly selected and divided into Groups B and C. Both groups received conventional treatment. Among them, Group C was given early CBP treatment. Another 60 healthy cases in physical examination at the same time were selected as Group A. The abundances of TLR4 and inflammatory factors were detected before and after treatment. Compared with Group B, (1) the symptoms in Group C improved more markedly; (2) protein contents of TLR4 and nuclear factor kappa B (NF‐κB) in Group C diminished more signally; (3) the abundances of tumor necrosis factor alpha (TNF‐α), cytokine interleukin‐1β (IL‐1β), and cytokine interleukin 6 (IL‐6) in Group C decreased (p < 0.05); and (4) the abundance of TLR4 in Group C was positively correlated with those of TNF‐α, IL‐1β, and IL‐6 after treatment (all p < 0.001). Early CBP inhibits TLR4 signaling pathway in SAP patients and attenuates the abundance of inflammatory factors to a certain extent, which may provide a new clinical treatment strategy for SAP.